A case of an 82-year-old man with a spinal extradural malignant ossifying fibromyxoid tumor - Lu, Qiqi (2023)
BACKGROUND: Ossifying fibromyxoid tumor (OFMT) is a rare mesenchymal tumor predominantly involving the subcutaneous tissues or skeletal muscles in the proximal extremities, typically in middle-aged men. OFMT in the spine is extremely rare, with only 3 previously reported cases in the literature. CASE REPORT: Here, we present a rare case of an 82-year-old man presenting with paresthesia of both arms and weakness of both legs, who underwent magnetic resonance imaging (MRI) of the spine, which showed an aggressive extradural tumor. Following surgical debulking, histology examination revealed a tumor of stromal origin with myxoid and ossifying components and pleomorphic features. Overall findings were suggestive of a malignant OFMT. The patient underwent postoperative adjuvant radiotherapy. However, the first follow-up MRI study at 8 months showed residual tumor, which also demonstrated avid tracer uptake on technetium-99m scintigraphy and PET-CT scans. The second MRI follow-up about 9 months later showed several metastatic foci along the craniospinal axis. Despite subsequent resection of the spinal metastasis, the patient eventually died of sepsis about 21 months after the initial tumor diagnosis. CONCLUSIONS: We presented a case of extradural spinal malignant OFMT and highlighted the difficulty distinguishing this rare primary tumor from spinal metastases. In this case, MRI signal intensities and identifying intratumoral bone formation, combined with histopathology following surgical resection, confirmed the diagnosis. This case has also shown the importance of follow-up by a multidisciplinary team to monitor for the recurrence of primary OFMT.